2020
DOI: 10.1111/nan.12645
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next‐generation sequencing of adult gliomas for retrospective prognostic evaluation and up‐front diagnostics

Abstract: Aims We aimed to reclassify a population‐based cohort of 529 adult glioma patients to evaluate the prognostic impact of the 2016 World Health Organization (WHO) central nervous system tumour classification. Moreover, we evaluated the feasibility of gene panel next‐generation sequencing (NGS) in daily diagnostics of 225 prospective glioma patients. Methods The retrospective cohort was reclassified according to WHO 2016 criteria by immunohistochemistry for IDH‐R132H, fluorescence in situ hybridization for 1p/19q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Interestingly, mutIDH1/2 do not appear to confer survival benefits in AML, 28 , 240 chondrosarcoma, 24 , 66 or ICC 37 , 241 but appear to do so in glioma. 242 Additionally, in chondrosarcoma, the response to radiation treatment does not correlate with mutIDH1/2-status. 243 Thus, the current understanding of mutIDH1/2 in relation to redox homeostasis is that it is cancer-type dependent.…”
Section: Altered Redox Homeostasis Linked To Mutant Idh1 Consumption Of Nadphmentioning
confidence: 99%
“…Interestingly, mutIDH1/2 do not appear to confer survival benefits in AML, 28 , 240 chondrosarcoma, 24 , 66 or ICC 37 , 241 but appear to do so in glioma. 242 Additionally, in chondrosarcoma, the response to radiation treatment does not correlate with mutIDH1/2-status. 243 Thus, the current understanding of mutIDH1/2 in relation to redox homeostasis is that it is cancer-type dependent.…”
Section: Altered Redox Homeostasis Linked To Mutant Idh1 Consumption Of Nadphmentioning
confidence: 99%
“…The survival curve of DAs was definitely favourable compared with AAs in the early course, and the generalized Wilcoxon test showed a significant difference. Taking IDH -mutation status into consideration, WHO grade was reported as a significant factor for OS in lower-grade gliomas 11 , 24 , 25 , and one of the studies showed that WHO grade had higher prognostic value in IDH -wild-type astrocytomas compared with in IDH -mutant astrocytomas, with the authors proposing histological mitotic count as a significant predictor of prognosis 24 . This fact supports the importance of histological grading systems, especially for IDH -wild-type astrocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…The survival curve of DAs was de nitely favourable compared with AAs in the early course, and the generalized Wilcoxon test showed a signi cant difference. Taking IDH-mutation status into consideration, WHO grade was reported as a signi cant factors for OS in lowergrade gliomas, 11,24,25 and one of the studies showed that WHO grade had larger prognostic value in IDHwild-type astrocytomas compared with in IDH-mutant astrocytomas, with the authors proposing histological mitotic count as a signi cant predictor of prognosis. 24 This fact supports that histological grading systems remain important, especially for IDH-wild-type astrocytoma.…”
Section: Discussionmentioning
confidence: 99%